2014
DOI: 10.3390/metabo4030599
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling of Root Exudates of Common Bean under Phosphorus Deficiency

Abstract: Root exudates improve the nutrient acquisition of plants and affect rhizosphere microbial communities. The plant nutrient status affects the composition of root exudates. The purpose of this study was to examine common bean (Phaseolus vulgaris L.) root exudates under phosphorus (P) deficiency using a metabolite profiling technique. Common bean plants were grown in a culture solution at P concentrations of 0 (P0), 1 (P1) and 8 (P8) mg P L−1 for 1, 10 and 20 days after transplanting (DAT). Root exudates were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 24 publications
(26 reference statements)
3
42
0
Order By: Relevance
“…The web-based resource PIFAR allowed the identification of 175 gene products in P. aeruginosa putatively involved in the interaction with plants (Martinez-Garcia et al, 2016) and the TlpQ chemoreceptor was found to mediate chemotaxis toward the plant hormone ethylene (Kim et al, 2007). αKG is present at significant levels in plant root exudates (Tawaraya et al, 2014; Ganie et al, 2015) and chemotaxis to root exudate components was shown to be essential for efficient root colonization (de Weert et al, 2002; Scharf et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…The web-based resource PIFAR allowed the identification of 175 gene products in P. aeruginosa putatively involved in the interaction with plants (Martinez-Garcia et al, 2016) and the TlpQ chemoreceptor was found to mediate chemotaxis toward the plant hormone ethylene (Kim et al, 2007). αKG is present at significant levels in plant root exudates (Tawaraya et al, 2014; Ganie et al, 2015) and chemotaxis to root exudate components was shown to be essential for efficient root colonization (de Weert et al, 2002; Scharf et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Subsequent experiments were aimed at elucidating whether McpG-mediated taxis alters colonization of plant roots. Previous studies have shown that significant amounts of GABA are present in root exudates of different plants (Penrose and Glick, 2001;Carvalhais et al, 2011;Badri et al, 2013;Tawaraya et al, 2014). We therefore conducted studies to determine whether GABA is present in root exudates of our model plant, the saladet tomato variety.…”
Section: Mcpg Of P Putida Kt2440r Participates In Attraction To and mentioning
confidence: 99%
“…Metabolites contained in common bean root exudates have been investigated in presence of different phosphorus concentrations. Organic acids and AA (Orn, Arg, Asp…) levels have been showing higher in the exudates in plants grown in absence of phosphate .…”
Section: Ce‐ms As a Metabolomic Toolmentioning
confidence: 97%